Waterpipe use among high school students in Ontario: Demographic and substance use correlates - Hamilton, Hayley A. (Can J Public Health, 2015)
OBJECTIVE: To examine waterpipe use and its association with demographic factors, tobacco cigarette smoking, ever use of electronic cigarettes (e-cigarettes) and alcohol use among high school students. METHODS: Data were derived from the 201 3 Ontario Student Drug Use and Health Survey, a school-based survey of 7(th) to 12(th) grade students. This province-wide survey was based on a stratified two-stage cluster design. Analyses were based on a subsample of 2,873 high school students and included adjustments for the complex sample design. RESULTS: Overall, 12.5% of high school students (grades 9-12) had used a waterpipe in the previous year. Awareness of waterpipes was high - 68.4% of students reported that they were aware of waterpipes but had not used one in the past year; 19.1 % had never heard of waterpipes or hookah. The percentage of high school students reporting waterpipe use in the past year was similar to reports of tobacco cigarette use (12.5% and 11 % respectively). Waterpipe use was highly associated with past-year tobacco cigarette and regular alcohol use as well as ever use of e-cigarettes. In multivariate analyses, males and females had similar odds of waterpipe use, and non-White students and those in higher grades had greater odds of use after controlling for other substance use. CONCLUSION: These findings suggest that waterpipe use among high school students should be of some concern and suggest the need for policy measures to address potential risks associated with use.